2019
DOI: 10.1111/jre.12646
|View full text |Cite
|
Sign up to set email alerts
|

Activation of vitamin D in the gingival epithelium and its role in gingival inflammation and alveolar bone loss

Abstract: Background and Objective Both chronic and aggressive periodontal disease are associated with vitamin D deficiency. The active form of vitamin D, 1,25(OH)2D3, induces the expression of the antimicrobial peptide LL‐37 and innate immune mediators in cultured human gingival epithelial cells (GECs). The aim of this study was to further delineate the mechanism by which vitamin D enhances the innate defense against the development of periodontal disease (PD). Materials and Methods Wild‐type C57Bl/6 mice were made def… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 47 publications
2
34
0
1
Order By: Relevance
“…Although we focused on hGFs, epithelial tissues were also observed in the present study, and gingival epithelia were found to be CYP27B1 positive in both groups, which was in line with the findings of other researchers (McMahon et al, 2011;Menzel et al, 2019). What should be pointed out is that the distribution of CYP27B1 expression differed between the two groups (Fig.…”
Section: Discussionsupporting
confidence: 93%
“…Although we focused on hGFs, epithelial tissues were also observed in the present study, and gingival epithelia were found to be CYP27B1 positive in both groups, which was in line with the findings of other researchers (McMahon et al, 2011;Menzel et al, 2019). What should be pointed out is that the distribution of CYP27B1 expression differed between the two groups (Fig.…”
Section: Discussionsupporting
confidence: 93%
“…Some studies have concluded that taking vitamin D may prevent the progression of periodontal disease ( 113 ). Menzel et al ( 114 ) have analyzed the relationship between vitamin D in the gingival epithelium and loss of alveolar bone, and suggested that dietary restriction of vitamin D leads to alveolar bone loss and increased inflammation in the gingiva. Boggess et al ( 115 ) have found that vitamin D and calcium supplementation increase jaw BMD and inhibit alveolar bone loss, and Garcia et al ( 116 ) have reported that supplementation with 800–1,000 IU vitamin D per day reduces the severity of periodontal disease.…”
Section: Effects Of Calcium Phosphorus and Vitamin D Imbalances On mentioning
confidence: 99%
“…Epithelial VDR signaling protects the integrity of the intestinal barrier by several mechanisms, including upregulation of junctional protein expression, stabilization of TJ structures, upregulation of cathelicidin (the precursor of LL-37) and β-defensins, and inhibition of inflammation-induced epithelial cell apoptosis (Sun 2010). Menzel et al (2019) reported that treatment of oral epithelial cells with 1,25(OH) 2 D 3 , the active form of vitamin D, upregulated LL-37 expression but downregulated inflammatory cytokine IL-1α. Interestingly, treatment of oral epithelial cells with 1,25(OH) 2 D 3 also reduced invasion by P. gingivalis , the mechanisms for which await further elucidation.…”
Section: Host Factors That Govern Bacterial Invasion Of Gingivamentioning
confidence: 99%